The Central Role of MGMP in Improving Teachers Digital Literacy - Sari Dewi, Ratna; Defianty , Maya; Zulfa, Siti; Anis Maulidia , Reza; Fatwa Mulyati, Yatni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Digital literacy is central for teachers as the skill can improve teachers’ instruction to be more effective. Nevertheless, studies showed that Indonesian teachers’ digital literacy is still relatively modest. This implies teachers need to be facilitated in enhancing their digital literacy; MGMP as the national professional learning community in Indonesia can potentially accommodate this particular need. This study aims to describe the role of MGMP in improving teachers’ digital literacy. This survey research involved 125 teachers who are active members of MGMP. The findings of this research showed 52% participants agreed that several activities in MGMP have supported them to improve their digital literacy such as collaborative discussions and sharing of best practices among teachers. Specifically, this collaborative environment can foster the exchange of digital tools and techniques that teachers can integrate into their teaching practices. Findings on this study also revealed that commonly MGMP include programs that inform teachers about digital tools, educational software, and online resources. These sessions help teachers to become more comfortable and proficient with digital technologies. This study has shed light on the potential role of MGMP in improving teachers’ digital literacy.